Inscription spatiale des trajectoires de recours aux soins à São Paulo et inégalités urbaines - Pauline Iosti (Confins)
The metropolis of São Paulo faces important socio-spatial inequalities, which are visible in the field of health. However, existing studies on health inequalities focus mainly on the logics of health care supply, and rarely on the actual health practices of individuals, or on their bypassing and negotiation practices. This article therefore seeks to contribute to a better understanding of health care inequalities, focusing on the spatialization of individual health trajectories in São Paulo. A qualitative methodology is adopted, based on the analysis of 43 semi-structured interviews, conducted between 2017 and 2018 in the neighbourhood of Vila Clara, and on the mapping of two of these trajectories. The results show, above all, the important spatial constraints faced by the population depending on public health care. We also demonstrate that all the populations negotiate in order to improve their health mobilities. However, these negotiations are unequally effective on the individuals' health spatialities. The trajectories of the population using the private health care subsystem are simpler, less dispersed in urban space and more in line with their daily mobility than those of users of public health care, who generally are more vulnerable. To conclude, the analysis of individual health trajectories proves to be a relevant approach to understanding health inequalities as well as urban inequalities.